The Health Behaviors of Patients with Diabetes Type 2’s towards Diabetes Remission Receiving Services from the Primary and Holistic Care Unit, Ban Na Hospital, Nakhon Nayok Province - Tantinantrakun, Supaporn; Yamsri, Thanaphon (Journal of The Royal Thai Army Nurses, 2025)
This descriptive study aimed to investigate health behaviors and specific psychological factors influencing diabetes patients preparing for the remission stage who received primary and holistic care services at Bann Na Hospital. A simple random sampling method was used, selecting 226 participants. Research instruments included a personal factor record form and questionnaires assessing perceived benefits, perceived barriers, self-efficacy, situational influence, interpersonal influence, and health behavior assessment. The reliability of the instruments was evaluated using Cronbach’s alpha coefficient, tested on 30 diabetes patients from a nearby area. The reliability values were 0.92, 0.96, 0.82, 0.89, 0.92, and 0.89, respectively. Data were analyzed using descriptive statistics and Pearson’s correlation coefficient. The findings revealed that participants exhibited moderate-level health behaviors (Mean=2.60, SD=0.28). Perceived benefits, perceived barriers, self-efficacy, and interpersonal influence were also at moderate levels, with mean scores of 3.30 (SD=0.74), 2.73 (SD=0.71), 3.06 (SD=0.44), and 2.12 (SD=0.21), respectively. However, the situational influence was at a low level (Mean=1.42, SD=0.14). Perceived benefits and self-efficacy were positively correlated with health behaviors at a significant level (P-value < .05, r=0.16) and (P-value < .01, r=0.23), respectively. The study suggests that Bann Na Hospital can utilize these findings to provide valuable insights into patients’ health behaviors, assisting physicians and nurses in preparing diabetes patients for the remission stage.